Convergence Problems in Indonesia: An Overview from Communication Perpective - Yudhawasthi, Ciwuk Musiana (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
Convergence occurs due to the storage of various knowledge sources in digital form. Unfortunately, in Indonesia, convergence has not yet become an option in providing knowledge services to the broader community on a massive scale. Although practitioners of documentary institutions have discussed this term frequently, they have not discussed how to carry out inter-institutional convergence. Convergence between documentary institutions is a common solution to improve accessibility, which is one way to increase the role of documentary institutions in the utilization and preservation of the nation’s collective memory. In the digital era, convergence must be interpreted broadly, not just as a physical union but more on the unification of function, substance, and communication. Communication problems are indeed the main problem hindering GLAMS convergence in Indonesia. This paper describes the convergence of documentary institutions from a communication perspective and motivates to build a more open communication pattern between documentary institutions. The dominant problem that hinders GLAMS convergence in Indonesia lies in communication issues